1997
DOI: 10.1016/s0022-5223(97)70051-5
|View full text |Cite
|
Sign up to set email alerts
|

Protection of rat spinal cord from ischemia with dextrorphan and cycloheximide: Effects on necrosis and apoptosis

Abstract: The results suggest that both N-methyl-D-aspartate receptor-mediated excitotoxicity and apoptosis contribute to spinal cord neuronal death after ischemia and that pharmacologic treatments directed at blocking both of these processes may have therapeutic utility in reducing spinal cord ischemic injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 25 publications
(6 reference statements)
0
14
0
3
Order By: Relevance
“…For example, cell loss induced by traumatic (Crowe et al, 1997;Liu et al, 1997) or ischemic (Kato et al, 1997;Mackey et al, 1997;Hayashi et al, 1998;Sakurai et al, 1998) spinal cord injury may be attributed, at least in part, to apoptotic mechanisms. Recently Springer et al (1999) reported that caspase-3 enzymatic activity increases as early as 1 hr after spinal cord trauma, along with cytochrome c release and caspase-9 processing.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cell loss induced by traumatic (Crowe et al, 1997;Liu et al, 1997) or ischemic (Kato et al, 1997;Mackey et al, 1997;Hayashi et al, 1998;Sakurai et al, 1998) spinal cord injury may be attributed, at least in part, to apoptotic mechanisms. Recently Springer et al (1999) reported that caspase-3 enzymatic activity increases as early as 1 hr after spinal cord trauma, along with cytochrome c release and caspase-9 processing.…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-3 is regarded as a critical executioner of apoptosis in several in vitro cell culture systems (Nicholson and Thornberry, 1997) and caspase-3 activation has been observed in vivo after TBI (Pike et al, 1998a;Yakovlev et al, 1997) and cerebral ischemia (Chen et al, 1998;Endres et al, 1998;Kitagawa et al, 1998;Namura et al, 1998). Apoptotic cell death has also been observed in animal models of TBI (Cólicos and Dash, 1996;Conti et al, 1998;Eldadah et al, 1996;Newcomb et al, 1999;Pravdenkova et al, 1996;Rink et al, 1995), spinal cord injury (Crowe et al, 1997;Kato et al, 1997;Katoh et al, 1996;Liu et al, 1997), and cerebral ischemia (Charriaut-Marlangue et al, 1998). Our laboratory has recently reported apoptotic cell death and independent or concurrent activation of calpains and caspase-3 proteases (Pike et al, 1998a) in various brain regions following lateral cortical impact traumatic brain injury in rodents.…”
Section: Introductionmentioning
confidence: 88%
“…Kato et al [20] have reported that neurons in the spinal cord undergo apoptosis after ischemic insults. These studies have two common features, in that morphological change suggestive of apoptosis is strongly expressed within 24 ∼ 48 hours after reperfusion among the ischemic spinal neurons, and that the apoptotic cells were scattered within areas that contained necrotic cells.…”
Section: Original Cardiovascularmentioning
confidence: 99%